Integration of wireless sensor networks into the distributed intelligent manufacturing within the framework of IEC 61499 function blocks - Abrishambaf, R.; Hashemipour, Majid; Bal, Mert (My University, 2011)
Wireless Sensor Networks (WSNs) is an emerging technology holding a great potential for distributed manufacturing automation. The WSN is not only a replacement of the conventional wired sensors, but is a technology that enhances flexible, distributed sensing, and collaborative information processing, which are vital elements for the distributed intelligent manufacturing control paradigm. Currently, the IEC 61499 function blocks have become an industry standard in distributed control for manufacturing automation. This standard has been empowered with the Multi-Agent Systems in a framework for added intelligence in manufacturing automation. In this paper, we explore the integration of the emerging WSN technology into this framework in order to enhance the flexibility and re-configurability through the wireless sensing and distributed information processing provided by a network of wireless sensors. We propose a three tiered model for integrating the WSN into the function blocks for realization of the distributed intelligent manufacturing control system. © 2011 IEEE.
2011 IEEE International Conference on Systems, Man, and Cybernetics, SMC 2011 --
Keywords: IEC 61499 Function Blocks; Intelligent Manufacturing; Multi-agent Systems; Wireless Sensor Networks